Sustainability and AgroTech: Analysis Model of Capabilities and Outcomes in University R+D Centers - Camio, Maria Isabel (2024)
This study identifies capabilities and innovation outcomes in the AgroTech sector with a focus on sustainability. A conceptual model is developed based on literature concerning university-industry linkages and innovation capabilities, operationalized through dimensions, variables, and indicators. The research site is the National University of the Center of the Province of Buenos Aires in Argentina, focusing on 14 scientific-technological activity nuclei (NACTs) with varying technological and relational capacities, developing products or services in the AgroTech sector with a sustainability focus. Academically, the study highlights the proposal of a model applicable to the analysis of R&D centers and useful indicators for measuring technological and relational capabilities. From a public policy perspective, the paper emphasizes the role of public research systems and suggests the creation of University-Industry collaboration spaces to address sustainability and territorial development challenges.